Electrical properties of metal-insulator-semiconductor (MIS) using low temperature deposition of ZnO as semiconductor layer: article / Saifullah Ali Harun - Harun, Saifullah Ali (2013)
This paper investigates the performance of low temperature zinc oxide (ZnO) film as semiconductor and poly(methyl methacrylate) (PMMA) as insulator layer in metalinsulator-semiconductor (MIS) structure. ZnO films were grown at different temperatures from 40oC, 60oC, 80oC, 100oC and 120oC. XRD result revealed that ZnO film grown at 120oC has (002) crystal structure with better crystallinity compared to the other temperatures. FESEM image show structure transformation of ZnO grain from rice shape to round shape at 120oC. MIS with ZnO grown at 120oC give the best electrical properties with current value of 38 x10-6 A and conductivity about 278 x 10-6 S/cm at 10V, compared to the other temperature. MIS with ZnO grown at 120oC indicate the highest dielectric constant, k with value of 7.7 at 1 KHz and 6.2 at 1 MHz. The best characteristics of MIS obtained from the structure with ZnO grown at 120oC due to high conductivity, high crytallinity, good surface morphology and high k value.